Development of Lateral Flow Test-System for the Immunoassay of Dibutyl Phthalate in Natural Waters - Anna N. Berlina; Maria Y. Ragozina; Nadezhda S. Komova; Kseniya V. Serebrennikova; Anatoly V. Zherdev; Boris B. Dzantiev (Biosensors, 2022)
The use of a large amount of toxic synthetic materials leads to an increase in the pollution of environmental objects. Phthalates are compounds structurally related to esters of phthalic acid that are widely used in the manufacturing of synthetic packaging materials as plasticizers. Their danger is conditioned by leaching into the environment and penetrating into living organisms with negative consequences and effects on various organs and tissues. This work presents the first development of lateral flow immunoassay to detect dibutyl phthalate, one of the most common representatives of the phthalates group. To form a test zone, a hapten–protein conjugate was synthesized, and gold nanoparticles conjugated with antibodies to dibutyl phthalate were used as a detecting conjugate. The work includes the preparation of immunoreagents, selectivity investigation, and the study of the characteristics of the medium providing a reliable optical signal. Under the selected conditions for the analysis, the detection limit was 33.4 ng/mL, and the working range of the determined concentrations was from 42.4 to 1500 ng/mL. Time of the assay—15 min. The developed technique was successfully applied to detect dibutyl phthalate in natural waters with recovery rates from 75 to 115%.